Effect of substituents in sulfoxides on the enhancement of thermoelectric properties of PEDOT:PSS: experimental and modelling evidence. Issue 5 (13th May 2020) - Zhu, Qiang; Yildirim, Erol; Wang, Xizu; Kyaw, Aung Ko Ko; Tang, Tao; Soo, Xiang Yun Debbie; Wong, Zicong Marvin; Wu, Gang; Yang, Shuo-Wang; Xu, Jianwei
Abstract : PEDOT:PSS doped with a series of functionalized sulfoxides exhibits enhanced electrical conductivity and Seebeck coefficient. Abstract : Poly(3, 4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS), being the most popular conductive polymer, has been doped with various additives with the aim of improving its thermoelectric performance. Among all additives, dimethyl sulfoxide (DMSO) has been widely used for various treatments. In this work, we designed and synthesized a series of aliphatic- and aromatic-substituted sulfoxides as dopants to improve the thermoelectric properties of PEDOT:PSS. It was found that the substituents in the sulfoxides played a vital role in controlling the thermoelectric properties. Sulfoxides with relatively longer alkyl chains and large phenyl groups increased the electrical conductivity of PEDOT:PSS to more than 200 S cm −1 compared to the pristine PEDOT:PSS film. The sulfoxide with 4-nitrophenyl substituents, however, led to negligible changes in electrical conductivity but increased the Seebeck coefficient from 22 to 56 μV K −1 . In contrast, the sulfoxide with 4-hydroxyphenyl substituents remarkably improved both the electrical conductivity and Seebeck coefficient, leading to a power factor of up to 69 μW m −1 K −2, much higher than that of the PEDOT:PSS film which was obtained by simply mixing with DMSO. Several simulation methods were used to evaluate various interactions between sulfoxides, PEDOT, and PSS to elucidate the mechanisms, revealing that the sulfoxide with 4-hydroxyphenyl groups exhibited additional interaction with the PSS phase, while the sulfoxide with 4-nitrophenyl groups showed strong interaction with the PEDOT phase instead and hence disrupted electrical conductivity. Our findings would uncover the mechanism of electrical conductivity enhancement, providing a general strategy for designing promising alternative additives for PEDOT:PSS treatment and eventually achieving better thermoelectric properties.